ZnO / CoWO4 composite material as well as preparation method and application thereof

The preparation of ZnO/CoWO4 composite material through electrospinning technology solved the problem of low light absorption efficiency in the visible and near-infrared spectral range of ZnO composite material, and achieved efficient photocatalytic and sterilization effects within the full spectrum range, suitable for multiple Application scenarios.

CN119140111APending Publication Date: 2024-12-17QILU UNIVERSITY OF TECHNOLOGY (SHANDONG ACADEMY OF SCIENCES)
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411286187.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-13
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

The existing ZnO composite materials have low light absorption efficiency in visible and near-infrared spectral ranges, which limits their photocatalytic and sterilization effects and cannot provide high photocatalytic and sterilization properties.

Method used

Through electrospinning technology, a ZnO/CoWO4 composite material is designed, using nanofiber morphology, adjusting the molar ratio of ZnO and CoWO4 and preparing methods, improving its light absorption capacity within the full spectrum range, and achieving efficient photocatalysis and sterilization.

Benefits of technology

It achieves efficient photocatalytic and sterilization effects under ultraviolet-visible and near-infrared light, improves the overall photocatalytic efficiency, and is suitable for multiple application scenarios, including pollutant degradation and environmental restoration.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119140111A_ABST
    Figure CN119140111A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of photocatalysis and application thereof, and particularly relates to a ZnO / CoWO4 composite material and a preparation method and application thereof. The composite material is prepared through a coaxial spinning technology, presents a one-dimensional hollow nanofiber structure, and is beneficial to transmission and separation of photo-induced electrons and holes, so that the oxidation-reduction reaction is effectively promoted, and the degradation efficiency is remarkably improved. The composite material has full-spectrum light absorption capability, and shows excellent light absorption performance in an ultraviolet-visible light region or an infrared light region, so that the degradation effect on tetracycline (TC) is remarkable under the irradiation of different light sources. In addition, the composite material is simple in preparation method, low in cost, good in cycling stability and convenient to recycle; pollutants in soil can be effectively degraded, and the problem of environmental pollution is relieved; the material shows a good sterilization effect under the irradiation of near-infrared light, avoids damage and energy consumption possibly brought by ultraviolet radiation, and has wide application potential in the fields of medical treatment and biology.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of photocatalysis and its application, and specifically relates to a ZnO / CoWO4 composite material and a preparation method and application thereof. Background Art

[0002] In order to protect human health and reduce ecosystem pollution, it is imperative to develop efficient, economical and environmentally friendly sterilization methods and new pollutant treatment technologies.

[0003] In recent years, the research on cobalt tungstate (CoWO4) in the field of photocatalysis has made significant progress. In order to improve the photocatalytic performance of cobalt tungstate, researchers have optimized its electronic structure and optical properties by doping different metal or non-metal elements. For example, doping with elements such as platinum (Pt) and molybdenum (Mo) can significantly improve the photocatalytic activity and stability of cobalt tungstate. Adjusting the morphology of cobalt tungstate (such as nanosheets, nanorods, and nanoparticles) has also been shown to effectively improve its photocatalytic performance. Different morphologies can affect the specific surface area and light absorption characteristics of the material, thereby changing its catalytic behavior. For example, the prior art (Zeoliticimidazolate framework grafted by cobalt tungstate as an efficient photocatalyst for photocatalytic oxidative desulfurization of dibenzothiophene[J], 2022, 149, 106894.) records that the ZIF-67@(1wt%) WO4 sample exhibits excellent photocatalytic oxidative desulfurization (PODS) activity (96.7%) among differently prepared photocatalysts. Another technology (Visible-light driven photocatalytic degradation of brilliant green dye based on cobalt tungstate (CoWO4) nanoparticles [J], 2018, 211, 355-342.) records that CoWO4 exhibits a monoclinic phase of wolframite structure, has high crystallinity and grows at a very high density. Within 120 minutes of visible light irradiation, about 94% of the basic brilliant green dye is degraded.

[0004] ZnO is considered to be an ideal candidate for bactericidal materials due to its good photocatalytic performance and biocompatibility. However, the weak light absorption of traditional ZnO in the visible light range limits its efficiency in photocatalytic reactions. Therefore, researchers began to explore enhancing its photoresponsive performance by doping or compounding ZnO. In recent years, zinc oxide (ZnO)-based composites have attracted widespread attention in the fields of photocatalysis and antibacterial. For example, the prior art (Photocatalytic performances of rare earth element-doped zinc oxide toward pollutant abatement in water and wastewater. Applied Catalysis B: Environment and Energy [J], 2019, 245, 159-166.) records that the photoactivity of ZnO doped with Ce, Er and especially Yb is higher than that of bare zinc oxide and benchmark TiO2 P25. Another prior art (Polyoxometalate anchored zinc oxide nanocomposite as a highly effective photocatalyst and bactericide for wastewater decontamination. Chemical Engineering Journal [J], 2023, 464, 142632.) reported that the nanocomposite material exhibited efficient photocatalytic degradation of tetracycline (TC, 90.75%), and the synergistic effect between ZnO@PDA and Cu-POMs destroyed the cell membrane, increased the level of oxidative stress, and caused bacterial death.

[0005] However, the spectral absorption range of the above ZnO composite materials is still limited, and they cannot provide high photocatalytic and bactericidal effects due to low absorption efficiency in the visible light and near-infrared spectral range. Summary of the invention

[0006] The prior art (Efficient wide-spectrum one-dimensional MWO4 (M = Mn, Co, and Cd) photocatalysts: Synthesis, characterization and density functional theory study. Journal of Colloid And Interface Science [J], 2024, 662, 822-835.) reported that the synthesized one-dimensional MWO (M = Mn, Co and Cd) material has enhanced light absorption capacity. In the range of 200-2000nm, cobalt tungstate nanofibers have the best photocatalytic performance. Under ultraviolet-visible light and near-infrared light irradiation, the removal rate of bisphenol A by CoWO4 nanotubes is 78.8% (140min) and 75.9% (12h), respectively. This study has brought new insights into the precise design of tungstate catalytic systems, promoted the development of ultraviolet-visible-near-infrared full-spectrum photocatalytic technology, and laid the foundation for a cleaner and more environmentally friendly future.

[0007] Since ZnO nanomaterials have good photocatalytic properties in the ultraviolet light region, and CoWO4 nanofibers have good photocatalytic properties in the full spectrum range, a ZnO / CoWO4 composite material is designed through electrospinning technology. It can not only utilize the photocatalytic properties of ZnO to perform efficient energy conversion in the ultraviolet light region, but also utilize the photoresponse properties of CoWO4 under near-infrared light to achieve targeted microbial inactivation. At the same time, it can also improve the overall photocatalytic efficiency in the full spectrum range, thus showing broad application prospects in multiple application scenarios.

[0008] Therefore, in view of the deficiencies in the prior art, the present invention provides a ZnO / CoWO4 composite material having the dual functions of efficient photocatalysis and near-infrared light efficient sterilization and a preparation method thereof.

[0009] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0010] A ZnO / CoWO4 composite material, characterized in that the composite material is composed of ZnO and CoWO4, the microstructure is nanofibers, the diameter of the nanofibers is 120-240nm; the molar ratio of ZnO to CoWO4 is (0.25-4):1.

[0011] The preparation method of the ZnO / CoWO4 composite material comprises the following steps:

[0012] (1) adding a tungsten source to an organic solvent and stirring evenly; adding a cobalt source and continuing to stir evenly; then adding a zinc source and further stirring evenly to obtain a mixed solution;

[0013] (2) slowly adding polyvinyl pyrrolidone to the mixed solution of step (1) in batches and stirring evenly to obtain a precursor solution;

[0014] (3) electrospinning the precursor solution of step (2) to obtain a fiber membrane;

[0015] (4) Calcine the fiber membrane described in step (3) at 520-550° C. to obtain a ZnO / CoWO4 composite nanofiber material.

[0016] Preferably, according to the present invention, in step (1), the mass volume ratio of the tungsten source to the organic solvent is (0.2-0.8):(5-20), in units of g / mL.

[0017] Preferably, according to the present invention, in step (1), the tungsten source is ammonium metatungstate or sodium tungstate;

[0018] Further preferably, in step (1), the tungsten source is ammonium metatungstate;

[0019] According to the preferred embodiment of the present invention, in step (1), the organic solvent is N,N-dimethylformamide or ethanol;

[0020] Further preferably, in step (1), the organic solvent is N,N-dimethylformamide.

[0021] According to the preferred embodiment of the present invention, in step (1), the cobalt source is cobalt acetate or cobalt nitrate;

[0022] Further preferably, in step (1), the cobalt source is cobalt acetate;

[0023] Preferably according to the present invention, in step (1), the zinc source is zinc acetate or zinc nitrate;

[0024] Further preferably, in step (1), the zinc source is zinc acetate.

[0025] Preferably, in step (1), a tungsten source is added to an organic solvent and stirred for 10-20 min; a cobalt source is added and stirred for 10-30 min; and a zinc source is added and stirred for 30-60 min.

[0026] Preferably according to the present invention, in step (1), the molar ratio of the cobalt source to the tungsten source is 1:1.

[0027] Preferably, in step (1), the molar ratio of the zinc source to the cobalt source is (0.25-4):1;

[0028] Further preferably, the molar ratio of the zinc source to the cobalt source is 0.25:1, 0.5:1, 1:1, 2:1, or 4:1.

[0029] Preferably according to the present invention, in step (2), the mass volume ratio of polyvinyl pyrrolidone to the mixed solution is (0.5-1.5):(5-15), in units of g / mL.

[0030] Preferably according to the present invention, in step (2), the polyvinyl pyrrolidone is K90 polyvinyl pyrrolidone.

[0031] Preferably according to the present invention, in step (2), the weight average molecular weight of polyvinyl pyrrolidone is 1.3 million.

[0032] According to the preferred embodiment of the present invention, in step (2), polyvinyl pyrrolidone is divided into 2-3 portions and gradually added to the mixed solution in 2-3 times. Polyvinyl pyrrolidone needs to be added slowly in batches. If a large amount of polyvinyl pyrrolidone is added at one time, stratification and agglomeration will occur.

[0033] Preferably according to the present invention, in step (2), after adding polyvinyl pyrrolidone, stirring is carried out for 8-12 hours.

[0034] Preferably, according to the present invention, the electrospinning method described in step (3) is as follows: the precursor solution is loaded into a syringe with a stainless steel needle, the receiving distance between the needle and the spinning receiving plate is 15-20 cm, the ejection rate of the precursor solution is 0.8-1.0 mL / h, the electrospinning voltage is 18-20 kV, the spinning temperature is 25-40°C, the spinning humidity is controlled at 10%-40%, the power is connected, the fiber membrane on the receiving plate is collected, and it is dried in an oven at 60°C for 12 hours.

[0035] Preferably, according to the present invention, the calcination method of step (4) is as follows: the fiber membrane is placed in a crucible and placed in a muffle furnace, and the temperature is raised to 520-550°C at a heating rate of 2°C / min in an air atmosphere, and then cooled to room temperature after keeping the temperature for 2 hours to obtain a ZnO / CoWO4 composite material.

[0036] Further preferably, in step (4), the temperature is raised to 550° C. at a heating rate of 2° C. / min in an air atmosphere.

[0037] The ZnO / CoWO4 composite material of the present invention is used for catalytic degradation of tetracycline under ultraviolet-visible light or near-infrared light, or for sterilization under near-infrared light.

[0038] The ZnO / CoWO4 composite material of the present invention has excellent photocatalytic performance in the full spectrum range, can be used to degrade organic matter, and provides a sustainable development solution for the efficient use of solar energy.

[0039] Compared with the prior art, this application has the following beneficial effects:

[0040] 1. The ZnO / CoWO4 composite material prepared by the coaxial spinning technology has a one-dimensional hollow nanofiber morphology, which is beneficial to the transmission and separation of photogenerated electrons and holes, and better redox reaction, thereby achieving a higher degradation efficiency.

[0041] 2. The ZnO / CoWO4 composite material of the present invention has full-spectrum light absorption capability and excellent light absorption in both the ultraviolet-visible light region and the near-infrared light region. Therefore, under different light sources, the effect of degrading tetracycline (TC) is more obvious.

[0042] 3. The ZnO / CoWO4 composite material prepared by the electrospinning technology of the present invention has low cost, simple technology, good cycle stability and is easy to recycle.

[0043] 4. The ZnO / CoWO4 composite material prepared by the present invention can effectively degrade pollutants in the soil, making the effectiveness of the polluted soil close to that of the unpolluted soil, thereby alleviating environmental pollution problems and promoting green development.

[0044] 5. The ZnO / CoWO4 composite material prepared by the present invention can fully achieve the sterilization effect under the irradiation of near-infrared light, can expand the full spectrum utilization of solar energy, avoid the damage and energy consumption that may be caused by ultraviolet radiation, and exert its potential for wide application in the medical and biological fields. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] Figure 1 The XRD spectra of the materials prepared in Examples 1-3 and Comparative Examples 1-2 are shown.

[0046] Figure 2 are SEM images of the materials, (a) is the SEM image of Example 1, (b) is the SEM image of Example 2, (c) is the SEM image of Example 3, and (d) is the particle size distribution diagram of Example 2.

[0047] Figure 3 TEM image (a), HRTEM images (b), (c), and element mapping image (d) of Example 2.

[0048] Figure 4 These are the N2 adsorption-desorption curves of the nanomaterials prepared in Examples 1-3 and Comparative Example 1.

[0049] Figure 5 The diffuse reflection absorption spectra of the nanomaterials prepared in Examples 1-3 and Comparative Examples 1-2 are shown.

[0050] Figure 6 The degradation graph (a) of tetracycline by the nanomaterials prepared in Examples 1-5 and Comparative Example 1 under irradiation with an ultraviolet-visible light source (200nm≤λ<760nm), and the degradation graph (b) of tetracycline by the nanomaterials prepared in Examples 1-5 and Comparative Example 1 under irradiation with a near-infrared light source (760nm≤λ<1600nm).

[0051] Figure 7 The impedance curves of the nanomaterials prepared in Examples 1-3 and Comparative Examples 1-2 are shown.

[0052] Figure 8 The materials obtained in Example 2 and Comparative Example 1-2 were irradiated with UV-visible light for 1 min. DMPO-·O2 - EPR spectrum (a), DMPO-·O2 under near-infrared light irradiation for 20 min - EPR spectrum of (b).

[0053] Fig. 9 The graphs are dotted lines showing the temperature change of the composite material prepared in Example 2 under irradiation with 808 nm laser light of different laser powers over time. In (a), the composite material is in a solid state, and in (b), the composite material is ultrasonically dispersed in water.

[0054] Fig.10 The composite material prepared in Example 2: Infrared thermal imaging image of the highest temperature that can be raised under sunlight (a), at 0.5 W / cm 2 Infrared thermal imaging of the highest temperature that can be reached under laser power (b), at 1W / cm 2 Infrared thermal imaging of the highest temperature that can be reached under laser power (c), ultrasonic dispersion in water at 1W / cm 2 Infrared thermal imaging of the highest temperature that can be reached under the laser power (d).

[0055] Fig.11 This is a diagram of plant growth in Application Experiment 1.

[0056] Fig.12 Figures 2 are the results of bacterial growth in Experimental Example 2, where (a), (b), and (c) are pictures of the composite material prepared in Example 2, after the E. coli solution was gradiently diluted to 10 times (a), 100 times (b), and 1000 times (c), and then spread on the culture medium for 12 hours; (d), (e), and (f) are pictures of the composite material prepared in Example 2 after the E. coli solution was gradiently diluted to 10 times, 100 times, and 1000 times, respectively, and then the composite material prepared in Example 2 was added, mixed, and then heated at 1 W / cm 2 The picture was taken after 5 minutes of 808nm laser irradiation with a laser power of 100 nm and 12 hours of growth on the culture medium.

[0057] Fig.13The results of the growth of E. coli in Experimental Example 2 are shown in Figures 1 and 2, where (a) and (b) are pictures of the E. coli solution after 12 hours of growth on the culture medium containing the materials of Comparative Examples 1 and 2; (c) and (d) are pictures of the E. coli solution after 12 hours of growth on the culture medium containing the materials of Comparative Examples 1 and 2 at 1 W / cm 2 After irradiation with 808 nm laser for 5 min, the images were taken after 12 h of growth on the culture medium. (ad) The dilution factor of the E. coli solution in the culture medium is 100 times. DETAILED DESCRIPTION

[0058] The present invention will be further described below in conjunction with specific embodiments, and the advantages and features of the present invention will become clearer as the description proceeds. However, the embodiments are exemplary only and do not constitute any limitation to the scope of the present invention. It should be understood by those skilled in the art that the details and forms of the technical solution of the present invention may be modified or replaced without departing from the spirit and scope of the present invention, but these modifications and replacements all fall within the scope of protection of the present invention.

[0059] Meanwhile, the experimental methods described in the following examples are conventional methods unless otherwise specified; the reagents and materials described are commercially available unless otherwise specified; and the equipment used are conventional equipment. Among them: polyvinyl pyrrolidone is polyvinyl pyrrolidone K90, with a weight average molecular weight of 1.3 million.

[0060] Example 1

[0061] The preparation method of ZnO / CoWO4 (Zn / Co molar ratio is 0.25:1) composite material comprises the following steps:

[0062] (1) Add 2 mmol of ammonium metatungstate to 10 mL of N,N-dimethylformamide solvent and stir for 10 min; add 2 mmol of cobalt acetate and stir for 10 min; then add 0.5 mmol of zinc acetate and stir for 30 min to obtain a mixed solution (volume 10 mL);

[0063] (2) Weigh 1 g of polyvinyl pyrrolidone K90 with a weight average molecular weight of 1.3 million, divide it into two equal parts, gradually add it into the mixed solution of step (1) in two portions, and stir for 8 hours to obtain a precursor solution;

[0064] (3) The precursor solution was loaded into a syringe with a stainless steel needle, the receiving distance between the needle and the spinning receiving plate was 15 cm, the ejection rate of the precursor sol was 0.8 mL / h, the electrospinning voltage was 20 kV, the spinning temperature was 25 ° C, the spinning humidity was controlled at 20%, and the power supply was connected to obtain the precursor fiber; the fiber film on the receiving plate was collected and dried in an oven at 60 ° C for 12 h;

[0065] (4) The dried fiber membrane was placed in a 25 mL crucible, placed in a muffle furnace, and heated to 550 °C at a rate of 2 °C / min under air atmosphere. After keeping the temperature for 2 h, it was cooled to room temperature to obtain a ZnO / CoWO4 (Zn / Co molar ratio of 0.25:1) composite nanofiber material.

[0066] Example 2

[0067] The preparation method of ZnO / CoWO4 (Zn / Co molar ratio is 0.5:1) composite material comprises the following steps:

[0068] (1) Add 2 mmol of ammonium metatungstate to 10 mL of N,N-dimethylformamide solvent and stir for 10 min; add 2 mmol of cobalt acetate and stir for 10 min; then add 1 mmol of zinc acetate and stir for 30 min to obtain a mixed solution (volume 10 mL);

[0069] (2) Weigh 1 g of polyvinyl pyrrolidone K90 with a weight average molecular weight of 1.3 million, divide it into two equal parts, gradually add it into the mixed solution of step (1) in two portions, and stir for 8 hours to obtain a precursor solution;

[0070] (3) The precursor solution was loaded into a syringe with a stainless steel needle, the receiving distance between the needle and the spinning receiving plate was 15 cm, the ejection rate of the precursor sol was 0.8 mL / h, the electrospinning voltage was 20 kV, the spinning temperature was 25 ° C, the spinning humidity was controlled at 20%, and the power supply was connected to obtain the precursor fiber; the fiber film on the receiving plate was collected and dried in an oven at 60 ° C for 12 h;

[0071] (4) The dried fiber membrane was placed in a 25 mL crucible, placed in a muffle furnace, and heated to 550 °C at a rate of 2 °C / min under air atmosphere. After keeping the temperature for 2 h, it was cooled to room temperature to obtain a ZnO / CoWO4 (Zn / Co molar ratio of 0.5:1) composite nanofiber material.

[0072] Example 3

[0073] The preparation method of ZnO / CoWO4 (Zn / Co molar ratio is 1:1) composite material comprises the following steps:

[0074] (1) Add 2 mmol of ammonium metatungstate to 10 mL of N,N-dimethylformamide solvent and stir for 15 min; add 2 mmol of cobalt acetate and stir for 20 min; then add 2 mmol of zinc acetate and stir for 40 min to obtain a mixed solution (volume 12 mL);

[0075] (2) Weigh 1 g of polyvinyl pyrrolidone K90 with a weight average molecular weight of 1.3 million, divide it into two equal parts, gradually add it into the mixed solution of step (1) in two portions, and stir for 10 hours to obtain a precursor solution;

[0076] (3) The precursor solution was loaded into a syringe with a stainless steel needle, the receiving distance between the needle and the spinning receiving plate was 15 cm, the ejection rate of the precursor sol was 0.8 mL / h, the electrospinning voltage was 20 kV, the spinning temperature was 25 ° C, the spinning humidity was controlled at 20%, and the power supply was connected to obtain the precursor fiber; the fiber film on the receiving plate was collected and dried in an oven at 60 ° C for 12 h;

[0077] (4) The dried fiber membrane was placed in a 25 mL crucible, placed in a muffle furnace, and heated to 550 °C at a rate of 2 °C / min under air atmosphere. After keeping the temperature for 2 h, it was cooled to room temperature to obtain a ZnO / CoWO4 (Zn / Co molar ratio is 1:1) composite nanofiber material.

[0078] Example 4

[0079] The preparation method of ZnO / CoWO4 (Zn / Co molar ratio is 2:1) composite material comprises the following steps:

[0080] (1) Add 2 mmol of ammonium metatungstate to 10 mL of N,N-dimethylformamide solvent and stir for 20 min; add 2 mmol of cobalt acetate and stir for 25 min; then add 4 mmol of zinc acetate and stir for 40 min to obtain a mixed solution (volume 12 mL);

[0081] (2) Weigh 1.5 g of polyvinyl pyrrolidone K90 with a weight average molecular weight of 1.3 million, divide it into two equal parts, gradually add it into the mixed solution of step (1) in two portions, and stir for 10 hours to obtain a precursor solution;

[0082] (3) The precursor solution was loaded into a syringe with a stainless steel needle, the receiving distance between the needle and the spinning receiving plate was 15 cm, the ejection rate of the precursor sol was 0.8 mL / h, the electrospinning voltage was 20 kV, the spinning temperature was 25 ° C, the spinning humidity was controlled at 20%, and the power supply was connected to obtain the precursor fiber; the fiber film on the receiving plate was collected and dried in an oven at 60 ° C for 12 h;

[0083] (4) The dried fiber membrane was placed in a 25 mL crucible, placed in a muffle furnace, and heated to 550 °C at a rate of 2 °C / min under an air atmosphere. After keeping the temperature for 2 h, it was cooled to room temperature to obtain a ZnO / CoWO4 (Zn / Co molar ratio is 2:1) composite nanofiber material.

[0084] Example 5

[0085] The preparation method of ZnO / CoWO4 (Zn / Co molar ratio is 4:1) composite material comprises the following steps:

[0086] (1) Add 2 mmol of ammonium metatungstate to 10 mL of N,N-dimethylformamide solvent and stir for 20 min; add 2 mmol of cobalt acetate and stir for 25 min; then add 8 mmol of zinc acetate and stir for 40 min to obtain a mixed solution (volume 13 mL);

[0087] (2) Weigh 1.5 g of polyvinyl pyrrolidone K90 with a weight average molecular weight of 1.3 million, divide it into two equal parts, gradually add it into the mixed solution of step (1) in two portions, and stir for 10 hours to obtain a precursor solution;

[0088] (3) The precursor solution was loaded into a syringe with a stainless steel needle, the receiving distance between the needle and the spinning receiving plate was 15 cm, the ejection rate of the precursor sol was 0.8 mL / h, the electrospinning voltage was 20 kV, the spinning temperature was 25 ° C, the spinning humidity was controlled at 20%, and the power supply was connected to obtain the precursor fiber; the fiber film on the receiving plate was collected and dried in an oven at 60 ° C for 12 h;

[0089] (4) The dried fiber membrane was placed in a 25 mL crucible, placed in a muffle furnace, and heated to 550 °C at a rate of 2 °C / min under air atmosphere. After keeping the temperature for 2 h, it was cooled to room temperature to obtain a ZnO / CoWO4 (Zn / Co molar ratio of 4:1) composite nanofiber material.

[0090] Comparative Example 1

[0091] (1) Add 2 mmol of ammonium metatungstate to 10 mL of N,N-dimethylformamide solvent and stir for 10 min; add 2 mmol of cobalt acetate and stir for 10 min to obtain a mixed solution (volume 10 mL);

[0092] (2) Weigh 1 g of polyvinyl pyrrolidone K90 with a weight average molecular weight of 1.3 million, divide it into two equal parts, gradually add it into the mixed solution of step (1) in two portions, and stir for 8 hours to obtain a precursor solution;

[0093] (3) The precursor solution was loaded into a syringe with a stainless steel needle, the receiving distance between the needle and the spinning receiving plate was 15 cm, the ejection rate of the precursor sol was 0.8 mL / h, the electrospinning voltage was 20 kV, the spinning temperature was 25 ° C, the spinning humidity was controlled at 20%, and the power supply was connected to obtain the precursor fiber; the fiber film on the receiving plate was collected and dried in an oven at 60 ° C for 12 h;

[0094] (4) The dried fiber membrane was placed in a 25 mL crucible, placed in a muffle furnace, and heated to 550 °C at a rate of 2 °C / min under air atmosphere. After keeping the temperature for 2 h, the temperature was cooled to room temperature to obtain CoWO4 nanofiber material.

[0095] Comparative Example 2

[0096] (1) Add 2 mmol of zinc acetate into 10 mL of N,N-dimethylformamide solvent and stir for 10 min to obtain a zinc acetate solution;

[0097] (2) Weigh 1 g of polyvinyl pyrrolidone K90 with a weight average molecular weight of 1.3 million, divide it into 2 equal parts, add it to the zinc acetate solution in step (1) in batches in 2 times, and stir for 8 hours to obtain a precursor solution;

[0098] (3) The precursor solution was loaded into a syringe with a stainless steel needle, the receiving distance between the needle and the spinning receiving plate was 15 cm, the ejection rate of the precursor sol was 0.8 mL / h, the electrospinning voltage was 20 kV, the spinning temperature was 25 ° C, the spinning humidity was controlled at 20%, and the power supply was connected to obtain the precursor fiber; the fiber film on the receiving plate was collected and dried in an oven at 60 ° C for 12 h;

[0099] (4) The dried fiber membrane was placed in a 25 mL crucible, placed in a muffle furnace, and heated to 550 °C at a rate of 2 °C / min in an air atmosphere. After keeping the temperature for 2 h, the temperature was lowered to room temperature to obtain ZnO nanomaterials.

[0100] The following analysis experiments were performed on the materials of Examples 1-5 and Comparative Examples 1-2:

[0101] XRD analysis: Figure 1 XRD spectra of the ZnO / CoWO4(0.25:1) composite material prepared in Example 1, the ZnO / CoWO4(0.5:1) composite material prepared in Example 2, the ZnO / CoWO4(1:1) composite material prepared in Example 3, the CoWO4 nanomaterial prepared in Comparative Example 1, and the ZnO nanomaterial prepared in Comparative Example 2. The XRD spectra show that the crystal phase structures of the ZnO / CoWO4(0.25:1), ZnO / CoWO4(0.5:1), and ZnO / CoWO4(1:1) composite materials are consistent with the CoWO4 phase in Comparative Example 1, and the relevant diffraction peaks of ZnO can be detected.

[0102] SEM test: Use a toothpick to pick up the ZnO / CoWO4 (0.25:1) composite material prepared in Example 1, the ZnO / CoWO4 (0.5:1) composite material prepared in Example 2, and the ZnO / CoWO4 (1:1) composite material prepared in Example 3, and coat them on the conductive glue. After gold spraying, perform SEM test on the materials. (a) is the SEM picture of the ZnO / CoWO4 (0.25:1) composite material prepared in Example 1, (b) is the SEM picture of the ZnO / CoWO4 (0.5:1) composite material prepared in Example 2, (c) is the SEM picture of the ZnO / CoWO4 (1:1) composite material prepared in Example 3, and (d) is the particle size distribution diagram of the ZnO / CoWO4 (0.5:1) composite material prepared in Example 2. Figure 2 It can be seen that the diameter of one-dimensional ZnO / CoWO4 nanotubes is 120-240nm. With the increase of zinc source, the particles on the surface of the nanotubes gradually increase, and the surface is uneven, which can provide more active sites.

[0103] TEM, HRTEM, and elemental mapping analysis: The TEM image (a), HRTEM images (b) and (c), and elemental mapping diagram (d) of the composite material of ZnO / CoWO4 (0.5:1) prepared in Example 2 are as follows: Figure 3 As shown, it can be seen that the one-dimensional ZnO / CoWO4 (0.5:1) composite material is a hollow structure with a tube wall thickness of about 5-10nm, which can provide more active sites for the reaction. From the HRTEM image, it can be seen that the (100) and (200) crystal planes of CoWO4 and the (101) crystal plane of ZnO form lattice folds at 0.468, 0.233, and 0.247nm, respectively. A new crystal plane is formed between the (100) crystal plane of CoWO4 and the (101) crystal plane of ZnO, indicating the successful construction of the ZnO / CoWO4 heterojunction. The element mapping also proves the existence of each element in the sample.

[0104] N2 adsorption-desorption analysis: N2 adsorption-desorption isotherms of the materials in Examples 1-3 and Comparative Example 1 are as follows Figure 4 Based on this, the specific surface area of ​​the ZnO / CoWO4 (0.25:1) composite material prepared in Example 1 is 20.972 m 2 / g, the specific surface area of ​​the composite material of ZnO / CoWO4 (0.5:1) obtained in Example 2 is 51.386m 2 / g, the specific surface area of ​​the ZnO / CoWO4 (1:1) composite material obtained in Example 3 is 44.874m 2 / g, the specific surface area of ​​the CoWO4 nanomaterial prepared in Comparative Example 1 is 17.519 m 2 / g. By comparison, it can be seen that the introduction of ZnO increases the specific surface area, increases the active sites, promotes the generation of reactive species, and ensures the smooth progress of the photocatalytic redox reaction.

[0105] UV-Vis DRS analysis: The UV-Vis DRS analysis results of Examples 1-3 and Comparative Examples 1-2 are as follows Figure 5 As shown in: The results show that the ZnO nanomaterial prepared in Comparative Example 2 has good light absorption only in the ultraviolet light region, and has no light absorption in the visible light and near-infrared light regions. The ZnO / CoWO4 (0.25:1) composite material prepared in Example 1, the ZnO / CoWO4 (0.5:1) composite material prepared in Example 2, and the ZnO / CoWO4 (1:1) composite material prepared in Example 3 all have light absorption in the full spectrum range, and in the near-infrared light region (760nm≤λ<1600nm), the light absorption value is stronger than that of the CoWO4 nanomaterial prepared in Comparative Example 1. Therefore, the ZnO / CoWO4 photocatalyst can make full use of solar energy to excite electrons and holes, and can also make full use of the energy of near-infrared light, which can also assist in the subsequent use of near-infrared light to increase temperature and sterilize.

[0106] Photocatalytic degradation of tetracycline (TC): The composite materials prepared in Examples 1-3 and Comparative Example 1 were applied to the photocatalytic degradation of tetracycline (TC) solution, the concentration of which was 20 mg / L, and the specific steps were as follows:

[0107] At room temperature, 40 mg of the composite material was added to 40 mL of tetracycline (TC) solution and magnetically stirred in a photochemical reactor for 30 min to achieve adsorption-desorption equilibrium. An 800 W xenon lamp was used to simulate reference sunlight, and the solution was taken once every 20 min and centrifuged. The absorbance was detected using a UV-2550 spectrophotometer.

[0108] The degradation diagram of tetracycline under UV-visible light source (200nm≤λ<760nm) (a) and the degradation diagram of tetracycline under near-infrared light source (760nm≤λ<1600nm) (b) are as follows. Figure 6 As shown in Figure 6 As can be seen from (a), Example 2 has the best photocatalytic degradation rate. The composite materials prepared in Example 1 and Examples 3-5 also have a high photocatalytic degradation rate under ultraviolet-visible light. The adsorption capacity and photocatalytic degradation capacity are both better than those of the nanomaterial prepared in Comparative Example 1. Figure 6As can be seen from (b), Example 2 also has the best photocatalytic degradation rate under near-infrared light, but the degradation efficiency of Examples 4 and 5 is much lower than that of Example 2, and is not much different from that of Comparative Example 1, indicating that the presence of an appropriate amount of ZnO can effectively alleviate the charge recombination phenomenon and provide highly active and highly selective sites for the entire reaction.

[0109] AC impedance analysis: The materials of Examples 1-3 and Comparative Examples 1-2 were subjected to impedance analysis. The results are as follows: Figure 7 As shown in , the size of the arc reflects the transmission ability of photocatalyst electrons. The smaller the radius, the easier it is for electrons to be transmitted. Figure 7 It can be seen that the ZnO / CoWO4 (0.5:1) composite material prepared in Example 2 has the smallest impedance and the largest electron transmission capacity, followed by Example 1. Therefore, the electron transmission capacity of the ZnO / CoWO4 composite material photocatalyst prepared in the present invention is superior to that of the CoWO4 material prepared in Comparative Example 1.

[0110] DMPO-·O2 - EPR spectrum: EPR spectrum analysis was performed on the materials of Example 2, Comparative Example 1 and Comparative Example 2. The results are as follows: Figure 8 As shown in . Figure 8 It can be seen that under the irradiation of ultraviolet visible light and near-infrared light, the ZnO / CoWO4 (0.5:1) composite material prepared in Example 2 can generate superoxide ion radicals, which have strong oxidizing properties and can react with the membranes and cell walls of microorganisms such as bacteria and viruses, resulting in damage to their structures and functions. This oxidation can quickly destroy the survival mechanism of microorganisms, thereby achieving the purpose of sterilization.

[0111] Near-infrared laser irradiation experiment: 1 g of the ZnO / CoWO4 (0.5:1) composite material prepared in Example 2 was weighed and irradiated at 0.5 W / cm 2 and 1W / cm 2 The temperature rise under the irradiation of 808nm laser light with high laser power was analyzed. The results are as follows Fig. 9 As shown in (a). The laser power is 0.5W / cm 2 When the solid temperature is raised to 169.1℃, the laser power is 1W / cm 2 When the solid is heated to a maximum of 258.2°C, it has an excellent photothermal heating effect. Fig. 9 In (b), the concentration of the selected ZnO / CoWO4 (0.5:1) nanomaterial is 1 mg / mL, and the irradiation field area is about 0.5 m 2 , laser power is 0.5W / cm 2 When the solution temperature rises to 54°C, the laser power is 1W / cm 2When the solution temperature rises to 66.4℃, the laser power is 1.5W / cm 2 The solution temperature can rise to 84°C, which is higher than the inactivation temperature of Escherichia coli.

[0112] Infrared thermal imaging analysis: The ZnO / CoWO4 (0.5:1) composite material in Example 2 was subjected to infrared thermal imaging analysis. The results are as follows: Fig.10 Middle: (a) 1g ZnO / CoWO4 (0.5:1) composite material can be heated up to 52.4℃ under sunlight, (b) when the laser power is 0.5W / cm 2 When the laser power is 1W / cm 2 When the laser power is 1 W / cm 2 When the temperature of the solution can rise to 66.4℃ at the highest, the concentration of ZnO / CoWO4 (0.5:1) nanomaterials is 1mg / mL.

[0113] Application Experiment Example 1

[0114] Remediation of contaminated soil

[0115] The soil was selected from under a tree in the library of Qilu University of Technology (Shandong Academy of Sciences), and after being retrieved, it was ground with a mortar, passed through a 60-mesh sieve, and the sieve was gently scrubbed with a brush until no more soil particles could pass through.

[0116] Blank group: 300 g of sieved soil was placed in the cultivation box, 40 mung bean and pea seeds were planted, watered normally every day, and the growth was observed.

[0117] Polluted group: Pour 300g of sieved soil and 50g of tetracycline powder into a mortar, grind for 30min, then pour into a cultivation box, plant 40 mung bean and pea seeds, water normally every day, and observe the growth.

[0118] Comparative Example 1: 300g of sieved soil, 50g of tetracycline powder, and 5g of CoWO4 nanomaterials prepared in Comparative Example 1 were poured into a mortar, ground for 30 minutes, and poured into a cultivation box. 40 mung bean and pea seeds were planted, watered normally every day, and the growth was observed. The results are as follows: Fig.11 as shown in .

[0119] Comparative Example 2: 300g of sieved soil, 50g of tetracycline powder, and 5g of ZnO nanomaterials prepared in Comparative Example 2 were poured into a mortar, ground for 30 minutes, and then poured into a cultivation box. 40 mung bean and pea seeds were planted, watered normally every day, and the growth was observed. The results are as follows: Fig.11 as shown in .

[0120] Example 2 group: 300g of sieved soil, 50g of tetracycline powder, and 5g of the composite material of ZnO / CoWO4 (0.5:1) prepared in Example 2 were poured into a mortar, ground for 30 minutes, and poured into a cultivation box. 40 mung bean and pea seeds were planted, watered normally every day, and the growth was observed. The results are as follows: Fig.11 as shown in .

[0121] from Fig.11 It can be seen that after 2 days, 4 days, and 6 days of growth, the growth of mung beans and peas in Example 2 group is almost the same as that in the blank group, including stem length, leaf length, germination rate, etc. are almost consistent with the blank group. In contrast, after 6 days of growth, the germination rate of Comparative Example 1 group, Comparative Example 2 group, and the pollution group was only 30%, there were no green leaves, and the growth was very poor. This shows that under light conditions, the ZnO / CoWO4 (0.5:1) photocatalyst can effectively degrade tetracycline in the soil and achieve the purpose of repairing the soil.

[0122] Application Experiment Example 2

[0123] NIR(-): After the E. coli solution was diluted to 10 times, 100 times, and 1000 times, the ZnO / CoWO4 (0.5:1) composite material prepared in Example 2 was added, and after mixing, 100 μL of the diluted bacterial solution was dripped on the culture medium in turn, and the culture medium was spread and grown for 12 hours. The phenomenon was observed. The results are as follows: Fig.12 (a), (b), (c). At the same time, the E. coli solution was gradient diluted to 100 times, and the CoWO4 and ZnO nanomaterials prepared in Comparative Examples 1 and 2 were added. After mixing, 100 μL of the diluted bacterial solution was dripped on the culture medium, and the culture medium was spread and grown for 12 hours. The phenomenon was observed. The results are as follows Fig.13 (a), (b).

[0124] NIR (+): E. coli solution was diluted to 10 times, 100 times, and 1000 times, and then the ZnO / CoWO4 (0.5:1) composite material prepared in Example 2 was added and mixed at 1 W / cm 2 After irradiation with 808nm laser power for 5 minutes, 100μL of diluted bacterial solution was added to the culture medium and spread on the culture medium for 12 hours to observe the phenomenon. The results are as follows Fig.12 (d), (e), (f). At the same time, the E. coli solution was diluted to 100 times, and the CoWO4 and ZnO nanomaterials prepared in Comparative Example 1 and Comparative Example 2 were added, mixed and heated at 1 W / cm 2 After irradiation with 808nm laser power for 5 minutes, 100μL of diluted bacterial solution was added to the culture medium, and the culture medium was spread and grown for 12 hours. The phenomenon was observed. The results are as follows Fig.13 (c), (d).

[0125] from Fig.12 It can be seen that without near-infrared light irradiation, the growth of E. coli solution in three groups (a), (b), and (c) with different dilution multiples of the composite material with ZnO / CoWO4 (0.5:1) added, as well as Fig.13 The growth conditions of the two groups of E. coli liquid (a) and (b) with a dilution factor of 100 and CoWO4 and ZnO nanomaterials added were as follows: uniform dispersion, uniform particle size, and good growth condition.

[0126] Fig.12 In the figure, under near-infrared light irradiation, the growth of three groups of E. coli solutions with different dilution ratios (d), (e), and (f) of the composite material with ZnO / CoWO4 (0.5:1) added were observed: except for one E. coli bacteria found in the E. coli solution diluted 10 times (d) after 12 hours of growth, the rest were completely inactivated.

[0127] Fig.13 The growth of E. coli in two groups (c) and (d) with different dilution ratios of CoWO4 and ZnO nanomaterials added: the number of E. coli in (c) is significantly reduced compared with (a), and there is no significant change in (d) compared with (b).

[0128] The above experiments fully confirm that ZnO / CoWO4 (0.5:1) composite materials have good photothermal properties and bactericidal ability compared with CoWO4 or ZnO nanomaterials.

Claims

1. A ZnO / CoWO4 composite material, characterized in that: The composite material is composed of ZnO and CoWO4, and has a microscopic morphology of nanofibers, wherein the diameter of the nanofibers is 120-240 nm; and the molar ratio of ZnO to CoWO4 is (0.25-4):

1.

2. The method for preparing the ZnO / CoWO4 composite material according to claim 1, characterized in that: The following steps are involved: (1) adding a tungsten source to an organic solvent and stirring evenly; adding a cobalt source and continuing to stir evenly; then adding a zinc source and further stirring evenly to obtain a mixed solution; (2) slowly adding polyvinyl pyrrolidone to the mixed solution of step (1) in batches and stirring evenly to obtain a precursor solution; (3) electrospinning the precursor solution of step (2) to obtain a fiber membrane; (4) Calcine the fiber membrane described in step (3) at 520-550° C. to obtain a ZnO / CoWO4 composite nanofiber material.

3. The preparation method according to claim 2, characterized in that: In step (1), the mass volume ratio of the tungsten source to the organic solvent is (1-4) g: (25-100) mL; Preferably, the tungsten source is ammonium metatungstate or sodium tungstate; Further preferably, the tungsten source is ammonium metatungstate; Preferably, the organic solvent is N,N-dimethylformamide or ethanol; More preferably, the organic solvent is N,N-dimethylformamide.

4. The preparation method according to claim 2, characterized in that: In step (1), a tungsten source is added to an organic solvent and stirred for 10-20 minutes; a cobalt source is added and stirred for 10-30 minutes; and a zinc source is added and stirred for 30-60 minutes.

5. The preparation method according to claim 2, characterized in that: In step (1), the molar ratio of the cobalt source to the tungsten source is 1:

1.

6. The preparation method according to claim 2, characterized in that: In step (1), the molar ratio of the zinc source to the cobalt source is (0.25-4):1; Preferably, the molar ratio of the zinc source to the cobalt source is 0.25:1, 0.5:1, 1:1, 2:1, or 4:

1.

7. The preparation method according to claim 2, characterized in that: In step (2), the mass volume ratio of polyvinyl pyrrolidone to the mixed solution is (1-3) g: (10-30) mL; Preferably, in step (2), the polyvinyl pyrrolidone is K90 polyvinyl pyrrolidone; Preferably, the weight average molecular weight of polyvinyl pyrrolidone is 1.3 million; Preferably, when adding polyvinyl pyrrolidone, it needs to be divided into 2-3 portions and gradually added to the mixed solution in 2-3 times; Preferably, in step (2), after adding polyvinyl pyrrolidone, stirring is carried out for 8-12 hours.

8. The preparation method according to claim 2, characterized in that: The electrospinning method described in step (3) is as follows: the precursor solution is loaded into a syringe with a stainless steel needle, the receiving distance between the needle and the spinning receiving plate is 15-20 cm, the ejection rate of the precursor sol is 0.8-1.0 mL / h, the electrospinning voltage is 18-20 kV, the spinning temperature is 25-40°C, the spinning humidity is controlled at 10%-40%, the power is connected, the fiber membrane on the receiving plate is collected, and it is dried in an oven at 60°C for 12 hours.

9. The preparation method according to claim 2, characterized in that: The calcination method of step (4) is as follows: placing the fiber membrane in a crucible and placing it in a muffle furnace, heating the temperature to 520-550° C. at a heating rate of 2° C. / min in an air atmosphere, keeping the temperature for 2 hours and then cooling it to room temperature to obtain a ZnO / CoWO4 composite material; Preferably, in step (4), the temperature is raised to 550° C. at a heating rate of 2° C. / min in an air atmosphere.

10. Use of the ZnO / CoWO4 composite material according to claim 1 or the ZnO / CoWO4 composite material obtained by the method according to any one of claims 2 to 9, characterized in that: The ZnO / CoWO4 composite material is used for catalytic degradation of tetracycline under ultraviolet-visible light and near-infrared light, or for sterilization under near-infrared light.